Perceptions of Malaysian local government managers on accountability typology - Othman, Rohana; Taylor, Dennis; Sulaiman, Maliah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
Accountability is a concept that has been difficult to clearly identify or measure. There is disagreement over definitions of accountability and a lack of empirical evidence about ways the concept might be dimensionalized, although there is agreement that it is multi-dimensional in nature. The aim of this study is to provide evidence of the existence of common types of accountability that are considered by departmental managers in local governments in Malaysia to be rendered by their particular departments. Drawing from a range of writings that have propounded different dimensions for the accountability construct, this study develops an instrument and administers it to departmental heads and their immediate subordinate manager in local government authorities throughout Malaysia. A three-cluster solution resulted from the data analysis, indicating an accountability typology that reduces to the three dimensions managerial/public accountability, fiduciary/compliance accountability and political accountability.